"Mere Measurement Plus": How Solicitation of Open-Ended Positive Feedback Influences Customer Purchase Behavior. (February 2017) - Bone, Sterling A.; Lemon, Katherine N.; Voorhees, Clay M.; Liljenquist, Katie A.; Fombelle, Paul W.; Detienne, Kristen Bell; Money, R. Bruce
In two studies (a longitudinal field experiment with an established business-to-consumer national chain, and a field experiment with a business-to-business software manufacturer), the authors demonstrate that starting a survey with an open-ended positive solicitation increases customer purchase behavior. Study 1, a longitudinal field experiment, shows that one year after the completion of a survey that began by asking customers what went well during their purchase experience, those customers spent 8.25% more than customers who had completed a survey that did not include the positive solicitation. Study 2 utlizes multiple treatment groups to assess the stepwise gains of solicitation, measurement, and solicitation frame. The results demonstrate (1) a mere solicitation effect, (2) a traditional mere measurement effect, and (3) an additional "mere measurement plus" effect of an open-ended positive solicitation; all effects increased customer spending. Specifically, starting a survey with an open-ended positive solicitation resulted in a 32.88% increase in customer spending relative to a survey with no open-ended positive solicitation. The findings suggest that firms can proactively influence the feedback process. Soliciting open-ended positive feedback can create positively biased memories of an experience; the subsequent expression of those memories in an open-ended feedback format further reinforces them, making them more salient and accessible in guiding future purchase behavior.